A model for system heat pricing in Poland from the perspective of district heating companies and the regulator - Niestępska, Małgorzata (Instal, 2024)
The update of the ‘Fit for 55’ package introduced by the amendment of the ETS, EE, RES and IED directives in 2023 poses enormous challenges for the energy sector and in particular the heating sector in terms of decarbonisation. The new iteration of the “Green Deal” and the “REPowerEU” concept puts the focus on a radical improvement of energy efficiency which means a successive shrinking of the heat market. With declining revenues, district heating companies are challenged on the one hand to maintain a competitive price in relation to the substitute offer of electricity heating, and on the other hand they have to make capital-intensive investments in greening and efficiency. The amendment to the Energy Efficiency Directive established a new definition of ‘efficient heating and cooling systems’ setting a deadline of 2050 for decarbonising district heating systems. Only 20% of Polish district heating systems meet the current definition, so the vast majority of Polish district heating systems are still not efficient. At the same time, an analysis of the economic situation of companies shows that they do not have sufficient funds for investment. Heat prices in Poland for licensed companies are fully regulated. The economic situation of the sector has been deteriorating for several years. In particular, companies producing heat in cogeneration, i.e. the most preferred in an efficient district heating system, are showing problems with profitability and liquidity. What is the reason for the unsatisfactory transformation dynamics of the district heating sector? How can this situation be rectified? Is a revision of heat price regulation principles crucial or is intensification of financial support sufficient? Should the heat price regulation model in Poland be liberalised following the German model or remain only slightly adjusted? These questions were answered by participants in a workshop organised by the Polish Heating Industry Chamber of Commerce during the 13th System Heat Market Conference on 27-29 February 2024 in Lublin.